The structure of Iconic Storytelling on TV. Master’s Dissertation of State Doctorate in Sciences and Letters - Serrano, Manuel Martín (Razón y Palabra, 2018)
In all societies the communicative function of the medium is subject to another control exercised by the Mediator. Our objective has been to study the conflictive relationships that exist between television as a medium, the "in ovo" carrier of an iconic culture and the Mediator Television, which is an institution of social control. There is in television performance, a code of mediation and a code of communication. While a social mediator exercises its function of ideological control using social codes (norms: coercions, prohibitions, etc.) that transmit value judgments, a means exerts its communicative function using logical codes (inclusions, dependencies, exclusions, etc.), that transmit relationship judgments. We try to show that all ideological coercion of reality can be expressed and produce its effects through the intermediation of logical constraints. In this thesis we wanted to show that mediating institutions can use a means of communication to destroy the type of communication that makes possible the new communication capabilities of this medium. Our contribution to the knowledge of social control mediated by the recourse to television, is at the theoretical and methodological time. It has consisted in showing that there are constrictions that reduce the possible variety of world views on television; that this mediation can be reflected in a narrative production model; that this mediating model, like any other, has a logical structure; and that the methodologies required to identify the structure of the mediating models and how they work can be developed. We have created those methods of analyzing mediation and we have applied and tested them to find out how it is, and how "The World Order through television" is generated.